2019
DOI: 10.1121/1.5134450
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bidirectional impulse turbines for thermoacoustic engines

Abstract: A bidirectional impulse turbine to convert thermoacoustic power into electricity is investigated. Experimental measurements are done with a loudspeaker for varying acoustic conditions and turbine loads. The results are used to characterize the turbine performance and compare it to steady flow turbomachinery and turbines in oscillating water columns. A dimensional analysis is done to identify the variables that influence the turbine performance, after which a scaling is determined that uniquely determines the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Furthermore, the maximum efficiency that can be reached for both cases is independent of the turbine load. Finally, just as shown for the unshrouded rotor in previous work, 8 it is found that the acoustic frequency has a negligible influence on the turbine efficiency for the shrouded rotor. It can therefore be said that the shrouded rotor outperforms the unshrouded rotor for all investigated operating conditions.…”
Section: Shrouded Rotorsupporting
confidence: 78%
See 3 more Smart Citations
“…Furthermore, the maximum efficiency that can be reached for both cases is independent of the turbine load. Finally, just as shown for the unshrouded rotor in previous work, 8 it is found that the acoustic frequency has a negligible influence on the turbine efficiency for the shrouded rotor. It can therefore be said that the shrouded rotor outperforms the unshrouded rotor for all investigated operating conditions.…”
Section: Shrouded Rotorsupporting
confidence: 78%
“…A more elaborate explanation about the experimental procedure, including processing, validation, and error estimation, can be found in previous work. 8 The raw data, processing scripts, and processed results for all experiments presented in this work can be found in a supplementary data publication. 11 The experimental setup is shown schematically in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In previous work, a bidirectional impulse turbine was characterized under thermoacoustic conditions to identify the relevant performance indicators, and provide rules of scaling. 6 Subsequently, the turbine has been optimized under thermoacoustic conditions to reach an efficiency of around 36%, 7 which is in the same order as found for OWCs. 8 For both OWCs and the previous work, the turbine is used under atmospheric conditions with air as a working fluid.…”
Section: Introductionmentioning
confidence: 85%